1969
DOI: 10.1097/00132586-196902000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isoproterenol on Survival in Canine Endotoxin Shock

Abstract: ATIEMPTS to evaluate therapy in patients having shock due to gram-negative microorganisms (endotoxin shock) are obscured by the lack of quantitative data on the natural course of human shock. The canine experimental model for studying endotoxin shock has provided basic information on the pathophysiology of this disorder.6 11,22,23 Agents that have altered the progress of canine endotoxin shock favorably have at timnes been beneficial in human subjects.17' 23 However, the management of human endotoxin shock sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1974
1974
1974
1974

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Experiments were conducted on a pair of dogs simultaneously. At 60 min after endotoxin, infusions of 5 ml/kg per hr with constant infusion pumps were started; one dog (group I) receiving 5%o dextrose and another (group II), dextrose and isoproterenol 7 (0.25 ,Ag/kg per min). In the first five pairs, infusion was given for 4 hr and in the remaining 13 pairs, for 12 hr.…”
Section: Endotoxin a Single Lot Of Escherichia Coli Endotoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were conducted on a pair of dogs simultaneously. At 60 min after endotoxin, infusions of 5 ml/kg per hr with constant infusion pumps were started; one dog (group I) receiving 5%o dextrose and another (group II), dextrose and isoproterenol 7 (0.25 ,Ag/kg per min). In the first five pairs, infusion was given for 4 hr and in the remaining 13 pairs, for 12 hr.…”
Section: Endotoxin a Single Lot Of Escherichia Coli Endotoxinmentioning
confidence: 99%
“…This drug has reversed the severe hemodynamic and pulmonary alterations in sheep (4) and has been confirmed in dogs (5,6). Isoproterenol has significantly reduced the mortality in canine endotoxin shock (7). Various studies have shown that it increases cardiac output (8), dilates lower respiratory airways, relaxes arterioles, constricts veins, increases ventilation (9) and improves function of the failing heart (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors, the sympathetic denervation (Palmiero et al 1962) or the preventive administration of alpha receptor blocking agents (Mc Kay 1969;Muller Berghaus et al 1967;Muller Berghaus 1969;Whitaker et al 1969) or beta receptor blocking agents (Berk et al 1967(Berk et al , 1969 should reduce the biological and clinical disorders of endotoxin shock (generalized Shwartzman reaction). According to others, the preventive administration of alpha receptor blocking agents (Kardos 1966;Mc Lean et al 1965) or beta receptor blocking agents (Halmagyi et al 1963;Vick et al 1965) should enhance consumptive coagulopathy whereas the alpha or beta stimulating agents (Starzecki et al 1968;Vick et al 1965) should have an opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…Αί καταστάσεις αύται εϊναι λίαν συχναί καί απαντούν επί μορφών τίνων πυελονεφρίτιδος καί περιτονίτιδος, επί των πλείστων περιπτώσεων shock εξ ήπατίτιδος ή κιρρώσεως 46 , πολλών καταστά σεων σηπτικού shock 20 • ένδοτοξικοΰ shock 25 . 64 καί σχεδόν άπασών των περιπτώσεων shock οφειλομένου εις σηψαιμίαν εκ θετικών κατά Gram μικροοργανισμών. Ή χορήγησις Ίσοπρεναλίνης υπό τάς υποτασικός ταύτας συνθήκας, μή επηρεάσασα σημαντικως την Μ.Α.Π., απέτυχε του να αύξηση το Π.Π.Α.…”
Section: εικών 14unclassified